Neutrophil-to-Lymphocyte Ratio, derived Neutrophil-to-Lymphocyte Ratio, Platelet-to-Lymphocyte Ratio and Lymphocyte-to-Monocyte Ratio as risk factors in critically ill COVID-19 patients, a single centered study. - Noor, Afshan; Akhtar, Fahim; Tashfeen, Sunila; Anwar, Nimra; Saleem, Bilal; Khan, Saleem Ahmed; Akram, Zaineb; Shahid, Samra (Journal of Ayub Medical College Abbottabad, 2021)
Background: A lot remains anonymous about the characteristics and laboratory findings that may evaluate poor outcomes in patients with Coronavirus disease 2019.The aim of this study was to determine the relationship of change in the peripheral blood factors of Neutrophil-to-Lymphocyte Ratio, derived-Neutrophil-to-Lymphocyte Ratio, Lymphocyte-to-Monocyte Ratio, and Platelet-to-Lymphocyte Ratio in hospitalized patients with COVID-19 and its severity. Methods: Cross-sectional analytical study was performed at Department of Haematology in Pak Emirates Military Hospital affiliated with Army Medical College, Rawalpindi, Pakistan from March-July 2020. We included 735 patients confirmed by real-time reverse transcriptase polymerase-chain-reaction test for subacute respiratory syndrome corona virus-2 of all ages, irrespective of gender and were classified in groups of severe and non-severe groups. Results: Data of blood and baseline characteristics were compared in between the two groups and found to be significant (p-value <0.001). The median age was 46.3 years, and 82 cases were only females. Receiver operator curve demonstrated larger area under the curve of NLR, d-NLR, and PLR and showed them as independent diagnostic biomarkers which were significantly associated with the severity of illness. Binary logistic regression performed in the form of forest plot also showed these factors were significantly linked with the severity (p-value <0.001). Conclusion: NLR, d-NLR, and PLR along with pre-existing co morbidities can be used as an independent biomarker for the poor clinical outcome of COVID-19 illness.